Prevalence and Correlates of Police Contact Anxiety among Male and Female Black Emerging Adults in St. Louis, Missouri. (5th January 2023) - Motley, Robert O; Chen, Yu-Chih; Masood, Yasir; Finner, Alyssa; Joe, Sean
Abstract: Anxiety disorders are among the most prevalent disorders for Black emerging adults ages 18 to 29 in America. Moreover, some Black emerging adults with a history of exposure to police use of force may experience police contact anxiety (PCA) symptoms during (e.g., unable to relax) or in anticipation of future police contacts (e.g., urge to avoid police), which may develop into an anxiety disorder. To explore this phenomenon, the current study assessed the prevalence and correlates of PCA symptoms for Black emerging adults. Data were collected from a sample of Black emerging adults ( N = 300). Univariate, bivariate, and ordinary least square regression analyses were done to estimate prevalence rates and correlates of PCA symptoms. PCA symptoms were moderately high for the sample, and participants who worked full-time were significantly less likely to have higher PCA symptoms because of seeing a video of police use of force in the media than those who were unemployed. Findings from the current study provide direction for future analyses focusing prospectively on prevalence, severity, and correlates of PCA symptoms. In addition, results suggest the importance of social work clinicians/practitioners assessing for PCA symptoms among their patients with a history of exposure to police use of force.